Development of alginate granules for thiophenic derivative 5CN06 delivery by ionotropic gelation - Medeiros, Kaline de Araújo (2022)
The use of biodegradable polysaccharides with gel forming capacity to produce granules has been reported, but there are no reports in the literature associated with new 2-aminothiophene derivatives, which have demonstrated selective antifungal biological activity. Thus, the objective of this study was to evaluate the formation of alginate granules for the delivery of the thiophenic derivative and Active Pharmaceutical Ingredient (API) 5CN06 by ionotropic gelation. An emulsion of 0.1% 5CN06, a 3% sodium alginate solution and a 10% CaCl2 solution was produced. The emulsion and the alginate were mixed under different volumes and, under drip, in the CaCl2 solution, the granules were formed. Changing the proportion of polymer interferes with this yield, which is equal to and above 79.50% ± 0.03. In acid medium, pH 1.2, the granule does not have a significant swelling rate after 180 min. In a pH 7.4 medium it dissolves due to the presence of Na+. Using 10 ml of the emulsion mixtures containing the drug and 10 ml of 3% sodium alginate solution, granules were obtained with better encapsulation efficiency (65.7%). The higher mixing ratio interfered in the swelling capacity and in the thermal stabilization of the drug. Thus, the study of this system was promising, from the experimental conditions, for the understanding of the formation of granules to release the thiophenic derivative compound 5CN06, with antifungal action.